PÉRSIO, SÁTIRA 4: UMA PROPOSTA DE TRADUÇÃO | PERSIUS, SATURAE 4: A TRANSLATION PROPOSITION - Cairolli, Fábio Paifer (Estudos Linguísticos e Literários, 2016)
Este artigo apresenta uma tradução poética da quarta sátira de Pérsio, poeta latino do século I d.C.. Antecede o texto a exposição dos critérios pelos quais adotei o dodecassílabo para traduzir. A tradução é acompanhada de anotações explicativas, nas quais são brevemente esclarecidas passagens obscuras ou aspectos culturais que demandam mediação. Abstract: This article presents a poetic translation of the fourth satire of Persius, a Latin poet from the first century A.D. The text is preceded by an explanation of the reasons for adopting a twelve-syllable verse to translate the Latin text. The translation is accompanied by brief notes that clarify obscure passages and explain cultural references necessary for the reader’s understanding.